Evaluating the Role of Genetic Variants on first‐line antiepileptic drug response in North India: Significance of SCN1A and GABRA1 Gene Variants in Phenytoin Monotherapy and its Serum Drug Levels. (1st June 2016) - Baghel, Ruchi; Grover, Sandeep; Kaur, Harpreet; Jajodia, Ajay; Rawat, Chitra; Srivastava, Ankit; Kushwaha, Suman; Agarwal, Rachna; Sharma, Sangeeta; Kukreti, Ritushree
Summary: Aim: The present study aimed to evaluate association of genetic variants on drug response and therapy optimization parameters in patients treated with first‐line antiepileptic drugs (AEDs). Genetic variants from ion channels, their functionally related genes, and synaptic vesicle cycle (SVC) genes with a potential role in epilepsy pathophysiology were thus prioritized. Methods: A total of 12 genes from ion channels and related gene set and seven genes from SVC comprising 155 SNPs were genotyped and evaluated with drug response, dose levels, and drug levels in 408 patients with epilepsy. Results: Both GABRA1 and SCN1A variants showed haplotypic and diplotypic associations in response to phenytoin (PHT). Diplotype analysis of GABRA1 variants revealed association of rs12658835|rs7735530 (AG/AG) ( P ‐valuecorrected  = 0.034, OR = 3.75, 95% CI = 1.36–11.05) and rs12658835|rs7735530|rs7732641|rs2279020 (AGCA/AGCA) ( P ‐valuecorrected  = 0.035, OR = 2.48, 95% CI = 0.96–6.41) with recurrent seizures. SCN1A haplotype rs6432860|rs3812718 (AC: P ‐valuecorrected  = 0.022, OR = 2.72, 95% CI = 1.39–5.35) and diplotype (AC/AC: P ‐valuecorrected  = 0.034, OR = 6.42, 95% CI = 1.10–65.76) were further observed to be associated with recurrent seizures. With respect to therapy optimization parameters, we observed significantly lower dose‐adjusted drug levels at maximum dose of PHT in patients carrying AC/AC diplotype ( P ‐value = 0.021). Conclusion: The results further substantiate the role of GABRA1 in PHT mode of action and contribution of SCN1A in response and therapy optimization with PHT monotherapy.